PENINGKATAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN EKSPLORASI BARANG BEKAS - Siti Trisnawarsi (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2016)
Creativity of children aged 5-6 years in kindergarten Al-Hidayah Pulo Ampel is still low, this factor caused by the learning activities that are still monotonous and make children feel bored and tired. This proved many children who lack creativity. Exploration activities thrift one approach adopted in the teacher foster creativity in children. The method used in this study is a research methods class action, action that is designed in a recurring cycle, in this study consisted of two cycles. In the first cycle of 8 times the action and the second cycle 2 times the action, with a 70% success criteria. Subjects in this study were in kindergarten Al-Hidayah Pulo Ampel with a total of 10 children aged 5-6 years which consists of 4 boys and 6 girls in each cycle consists of three phases, namely, planning, action and observation and reflection. The technique of collecting data through observation, field notes, interview notes and documentation. Data analysis using data reduction, data presentation and conclusion. The analysis of the data shows that the creativity of children aged 5-6 years through exploration activities thrift in TK Al-Hidayah Pulo Ampel done as much as two cycles, the first cycle of 8 meetings and the second cycle as much as 2 meetings, given the early stage in the process RPPH learning by designing and implementing exploration activities thrift in learning, the core activities carried out by providing measures through activities make the construction and observation in each cycle. Based on the research results obtained that the creativity of children aged 5-6 years through exploration activities thrift with the results of this research note that in the first cycle of data obtained reached 45% as an indicator of success reached 61%. This research was continued in the second cycle to the implementation of activities as much as 2 meetings obtained yield was 91%. Based on the results of the data that has been obtained, it can be concluded that the exploration activities of second-hand goods can enhance the creativity of children aged 5-6 years in kindergarten Al-Hidayah Pulo Ampel.